A PRELIMINARY ACCOUNT OF PRIMARY PRODUCTION AND ITS RELATION TO FISHERIES OF THE INSHORE WATERS OF THE GULF OF MANNAR - Raghu Prasad, R; Ramachandran Nair, P V (Indian Journal of Fisheries, 2015)
In the ecological studies of marine environments dynamics of production and the quantitative aspects of the relations involved have received special interest. Such quantitative studies of the various relationships have resulted in the familiar ’Eltonian Pyramid’ which represents the layering of the community brought about by the feeding habits of different species. But due to the inevitable loss of materials at each level in the food chain the yield normally will be smaller than the supply. According to Clarke (1946) "the measurement of the ratio of yield to supply, and hence the efficiency of the formation of the yield, is therefore of great importance to the ecologist, to the conservationist, and to the farmer or fishermen, in order to ascertain whether the actual yield represents a needlessly low utihzation or an overexploitation of the area.